2021
DOI: 10.1107/s2053230x21009250
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the complex of DNA with the C-terminal domain of TYE7 from Saccharomyces cerevisiae

Abstract: TYE7, a bHLH (basic helix–loop–helix) transcription factor from Saccharomyces cerevisiae, is involved in the regulation of many genes, including glycolytic genes. Meanwhile, accumulating evidence indicates that TYE7 also functions as a cyclin and is linked to sulfur metabolism. Here, the structure of TYE7 (residues 165–291) complexed with its specific DNA was determined by X-ray crystallography. Structural analysis and comparison revealed that His185 and Glu189 are conserved in base recognition. However, Arg19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…For all the target genes regulated by these potential TFs, only 2 genes in 336 genes regulated by Met32p were DEGs in C_T vs. C_S group. This indicated that the regulatory mechanisms of Tye7p and its regulated TFs during mixed sugar fermentation were possibly very different from those with the fermentation of glucose under the conditions of most researchers studied [ 34 , 35 ]. Hence, further studies are needed to reveal the genes they regulate and the contributions of these TFs to xylose metabolism and inhibitor tolerance.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…For all the target genes regulated by these potential TFs, only 2 genes in 336 genes regulated by Met32p were DEGs in C_T vs. C_S group. This indicated that the regulatory mechanisms of Tye7p and its regulated TFs during mixed sugar fermentation were possibly very different from those with the fermentation of glucose under the conditions of most researchers studied [ 34 , 35 ]. Hence, further studies are needed to reveal the genes they regulate and the contributions of these TFs to xylose metabolism and inhibitor tolerance.…”
Section: Resultsmentioning
confidence: 94%
“…Tye7p, a transcriptional activator, contributes to glycolytic genes activation, such as ENO1 and ENO2 (enolase), TDH (glyceraldehyde-3-phosphate dehydrogenase), PGK1 (phosphoglycerate kinase), PGM1 (phosphoglycerate mutase), PYK1 (pyruvate kinase), and TPI1 (triosephosphate isomerase) [ 32 , 33 ]. Researchers have revealed that Tye7p involves in the positive regulation of the glycolytic process and activates Ty1 mRNA transcription [ 34 , 35 ]. However, the regulation mechanism of Tye7p in response to inhibitors has not been reported.…”
Section: Introductionmentioning
confidence: 99%